Euler's theorem for homogenic functions states, that an $f:\mathbb{R}^n\to\mathbb{R}$, continuously differentiable function is homogeneous of degree $k$ if and only if for all $r \in \mathbb{R}^n$ the following equation satisfies. $$\sum_{i=1}^nr_i\partial_if(r)=kf(r)$$ A proof my professor did was fine for the part where we start from the fact that $f$ is homogeneous, so then the equation is satisfied. The other part is where I have problems, when we start from the fact that the upper equation is true.

He did the following: Define $g:\mathbb{R}\to\mathbb{R}$ to be $g(t) = \frac{f(tr)}{t^k}$ where $t>0$. By the theorem's criterions we know that $g$ is differentiable (since $f$ is continuously differentiable). Taking the derivative of $g$ we get: $$g'(t) = \frac{\sum_{i=1}^nr_i\partial_if(tr)t^k-kt^{k-1}f(tr)}{t^{2k}} = \frac{\sum_{i=1}^n(tr_i)\partial_if(tr)-kf(tr)}{t^{k+1}} = 0$$ By the criterion, this is zero, and this is where we finished, the theorem is proven. It's not clear how does this finish the proof. Didn't we simlply proved, that $g$ is a constant function, so $f(tr) = ct$ for some $c\in\mathbb{R}$? How can the original statment be deducted from this, that $f$ is homogeneous, by definition, the $f(tr) = t^kf(r)$ equation holds?

Edit: What I thought first is that we can maybe define $g$ to be $g(t) = \frac{f(tr)}{t^kf(r)}$. But then we have no criterion so that $f(r) \neq0$, so it seems incorrect. But even by doing this I'd still have the problem with it simply being a constant function, hence not being able to get rid of the $c$ constant. It seems like I can't notice something.

  • 2
    $\begingroup$ The constant is $g(1)=f(r)$. Therefore $f(tr)/t^k=f(r)$. $\endgroup$ – Jens Schwaiger May 14 '18 at 20:52
  • $\begingroup$ Ohh, since $g$ is constant and we know $g(1)$ to be $f(r)$, then $g(t) = f(r)$ for every $t$. I think I understand now. $\endgroup$ – Levente Kovács May 14 '18 at 20:55

Thanks Jens Schwaiger for the tip in the comments, the credit is his, I'm just going to post it as an answer.

By showing that $g$ is a constant function, we can plug in any $t > 0$ value to $g$ and that will give us the constant. Plugging in $1$ we get that $g(1) = f(r)$, hence $g(t) = f(r)$ for every $t>0$. $$\frac{f(tr)}{t^k}=f(r)$$ Reordering this we get the desired result, which is: $$f(tr) = t^kf(r)$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.